Composite coating electrode, preparation method thereof and battery
By using a composite coating electrode structure in the battery, the low thermal expansion coefficient material of the second coating is used to suppress the expansion of the phosphorus carbon coating, and the problem of volume expansion of the phosphorus carbon composite anode material during the deintercalation of lithium ions is solved, which extends the The cycle life of the battery.
Patent Information
- Application Number
- CN202310721396.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
The volume expansion of the phosphorus-carbon composite anode material during the deintercalation of lithium ions leads to damage to the electrode, affecting the battery cycle life.
The composite coating electrode structure is adopted, wherein the first coating is a phosphorus-carbon composite material, the thermal expansion coefficient of the second coating is smaller than that of the first coating, and is located outside the first coating along the electrode thickness direction to suppress the expansion of the phosphorus-carbon coating. .
It effectively inhibits the expansion of the phosphorus-carbon coating, avoids the peeling of the negative electrode active material, and extends the cycle life of the battery.
Smart Images

Figure CN119153624A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the field of battery technology, and in particular to a composite coating electrode and a preparation method thereof, and a battery. Background Art
[0002] With the emergence of new markets such as electric vehicles (EV) and hybrid electric vehicles (HEV), there is a huge demand for lithium-ion batteries (LIB). As one of the core materials of lithium-ion batteries for new energy vehicles, negative electrode materials play a vital role in the final performance of new energy vehicles. As an emerging negative electrode material, phosphorus-based negative electrodes have the advantages of low price, abundant reserves, environmental friendliness, and high specific capacity, and have gradually become the focus of negative electrode research.
[0003] However, although the expansion properties of the phosphorus-carbon composite negative electrode material formed by combining the phosphorus-based negative electrode material with carbon have been greatly improved, the phosphorus-carbon composite negative electrode material still has the problem of volume expansion during the process of lithium ion insertion and extraction, resulting in electrode damage, which affects the cycle life of the battery.
[0004] Therefore, how to optimize the volume expansion of phosphorus-carbon batteries to extend the battery cycle life has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0005] The technical problem solved by the embodiments of the present invention is how to optimize the volume expansion of phosphorus-carbon batteries.
[0006] In order to solve the above problems, an embodiment of the present invention provides a composite coating electrode, comprising:
[0007] Anode current collector;
[0008] A first coating layer attached to the surface of the negative electrode current collector, wherein the first coating layer comprises a first active material, and the first active material is a phosphorus-carbon composite material;
[0009] The second coating layer is attached to the surface of the first coating layer, and the second coating layer includes a second active material, and the thermal expansion coefficient of the second active material is smaller than the thermal expansion coefficient of the first active material.
[0010] Optionally, the second active material is at least one of graphite, hard carbon, soft carbon, and lithium titanate.
[0011] Optionally, the mass percentage of the first active substance is 70% to 95%.
[0012] Optionally, the mass percentage of the second active substance is 90% to 96%.
[0013] Optionally, the first coating has a thickness of 15 to 45 μm.
[0014] Optionally, the second coating has a thickness of 20 to 60 μm.
[0015] Optionally, the first coating includes a first binder, and the first binder is at least one of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.
[0016] Optionally, the second coating layer includes a second binder, and the second binder is at least one of CMC and SBR.
[0017] Optionally, the negative electrode current collector is at least one of copper foil, aluminum foil or carbon-coated aluminum foil.
[0018] To solve the above problems, an embodiment of the present invention further provides a method for preparing the above composite coating electrode, the preparation method comprising:
[0019] 1) preparing a slurry for the first coating layer and a slurry for the second coating layer;
[0020] 2) coating the dispersed slurry of the first coating layer on the negative electrode current collector and fully drying it;
[0021] 3) Using the pole coil coated with the first coating as the substrate, coating the dispersed slurry of the second coating on the surface of the first coating, and fully drying;
[0022] Repeat steps 2) and 3) to complete double-sided coating of the negative electrode current collector, and obtain the desired composite coating electrode after drying, rolling, slitting and cutting.
[0023] Optionally, the first coating and / or the second coating is coated by roller coating or spray coating.
[0024] Optionally, the coating thickness of the first coating slurry is 15 to 45 μm; the coating thickness of the second coating slurry is 20 to 60 μm.
[0025] To solve the above problems, an embodiment of the present invention further provides a battery, comprising:
[0026] Positive electrode, separator, electrolyte and the aforementioned composite coating electrode.
[0027] Compared with the prior art, the technical solution of the embodiment of the present invention has the following advantages:
[0028] The composite coating electrode provided by the embodiment of the present invention includes a first coating attached to the negative electrode current collector and a second coating attached to the first coating, the first coating is a phosphorus-carbon coating, the expansion coefficient of the second active material of the second coating is smaller than the expansion coefficient of the phosphorus-carbon composite material, and the second coating is arranged on the outside of the first coating along the thickness direction of the electrode. During the operation of the battery, the volume expansion change of the second coating is smaller than the volume expansion change of the first coating. The second coating with a smaller expansion coefficient located in the first coating can "hoop" the first coating to inhibit the expansion of the phosphorus-carbon coating and avoid the negative electrode active material from peeling off the current collector during a long cycle. Compared with a pure phosphorus-carbon electrode, the composite coating electrode provided by the embodiment of the present invention can improve the volume expansion problem of phosphorus-carbon system batteries and extend the battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0030] Figure 1 A schematic diagram of the structure of a composite coating negative electrode provided in an embodiment of the present application;
[0031] Among them, 1-current collector; 2-first coating; 3-second coating. DETAILED DESCRIPTION
[0032] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0033] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0036] Terms and Definitions
[0037] PVDF-Polyvinylidene fluoride CMC-Sodium carboxymethyl cellulose
[0038] SBR-Styrene Butadiene Rubber PAA-Acrylic Acid Homopolymer
[0039] PAA-Na-Sodium Polyacrylate PAA-Li-Lithium Polyacrylate
[0040] PP / PE / PP-Polypropylene / Polyethylene / Polypropylene
[0041] As known from the background technology, the phosphorus-carbon composite material as the negative electrode active coating expands in volume during the process of lithium ion insertion and extraction, causing electrode damage and affecting the battery cycle life.
[0042] It should be noted that the volume expansion of the phosphorus-carbon negative electrode in the present application refers to the expansion of the phosphorus-based negative electrode coating at the overall level of the coating during battery operation, which is the volume expansion caused by the peeling of the negative electrode active material (phosphorus-carbon composite material) from the current collector during long cycles.
[0043] In order to solve the above problems, an embodiment of the present invention provides a composite coating electrode, comprising:
[0044] Negative electrode current collector 1;
[0045] A first coating 2, attached to the surface of the negative electrode current collector, the first coating comprising a first active material, and the first active material is a phosphorus-carbon composite material;
[0046] The second coating layer 3 is attached to the surface of the first coating layer. The second coating layer includes a second active material. The thermal expansion coefficient of the second active material is smaller than the thermal expansion coefficient of the first active material.
[0047] It should be noted that if Figure 1 As shown, the first coating 2 is attached to the surface of the negative electrode current collector 1, which means that the first coating 2 is attached to the upper surface and / or lower surface of the negative electrode current collector 1 along the thickness direction of the current collector. The second coating 3 is attached to the surface of the first coating 2, which means that the second coating is attached to the outer surface of the first coating along the thickness direction of the current collector, and the second coating 3 is located outside the first coating 2 in the direction away from the negative electrode current collector. Because the thermal expansion coefficient of the second active material of the second coating is smaller than the thermal expansion coefficient of the phosphorus-carbon composite material, the volume expansion change of the second coating is smaller than the volume expansion change of the first coating during the operation of the battery. The second coating located outside the first coating and having a smaller thermal expansion coefficient can "hoop" the first coating to inhibit the expansion of the first coating (phosphorus-carbon coating) and avoid the negative electrode active material from peeling off the current collector during a long cycle. Compared with the pure phosphorus-carbon electrode, the composite coating electrode provided in the embodiment of the present invention can improve the volume expansion problem of the phosphorus-carbon system battery and extend the battery cycle life.
[0048] The first coating is directly coated on the negative electrode current collector, and the first coating consists of a first active material, a first conductive agent, and a first binder, wherein the first active material is a phosphorus-carbon composite material, and the mass percentage of the first active material is 70% to 95%, for example, 75%, 80%, 85%, 90%.
[0049] Phosphorus-carbon composite materials refer to phosphorus / carbon composite materials prepared by sublimation condensation method, high temperature adsorption method or high temperature ball milling method.
[0050] The first binder used in the first coating is one or a combination of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.
[0051] The first conductive agent includes at least one of conductive carbon black and carbon nanotubes.
[0052] The second coating is directly coated on the surface of the first coating, and is composed of a second active material, a second conductive agent, and a second binder, wherein the second active material is one or a combination of graphite, hard carbon, soft carbon, and lithium titanate, and the mass percentage of the second active material is 90% to 96%, for example, 91%, 92%, 93%, 94%, and 95%.
[0053] The thickness of the second coating layer should not be too thick or too thin. If the thickness of the second coating layer is too thin, it will not be able to effectively inhibit the expansion of the first coating layer (phosphorus-carbon coating layer). If the thickness of the second coating layer is too thick, it will affect the comprehensive performance of the battery, such as the electrical performance. Therefore, in a specific embodiment, the thickness of the second coating layer is 20 to 60 μm, for example, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm.
[0054] Taking into account factors such as the total thickness of the coating and from the actual process conditions, the thickness of the first coating can be 15 to 45 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm.
[0055] In order to further improve the thermal stability of the composite coating electrode, the thickness of the second coating can be approximately greater than or equal to the thickness of the first coating. For example, the thickness of the second coating exceeds the thickness of the first coating by ≥2 μm, specifically, 5 μm, 10 μm, 15 μm, 20 μm.
[0056] The second binder used in the second coating layer is at least one of CMC and SBR.
[0057] The second conductive agent includes at least one of conductive carbon black and carbon nanotubes.
[0058] The first coating layer and / or the second coating layer is coated by rolling or spraying.
[0059] The negative electrode current collector used in the negative electrode is one of copper foil, aluminum foil or carbon-coated aluminum foil.
[0060] The preparation process of the composite coating electrode includes the following steps:
[0061] 1) using a disperser to prepare a slurry for the first coating and a slurry for the second coating;
[0062] 2) coating the dispersed first coating slurry on the negative electrode current collector and fully drying it;
[0063] 3) Using the pole coil coated with the first coating as the substrate, apply the dispersed second coating slurry on the surface of the first coating and fully dry it;
[0064] Repeat steps 2) and 3) to complete double-sided coating and drying of the negative electrode current collector;
[0065] The dried pole coil is rolled using a roller press;
[0066] The electrode roll after rolling is cut and sliced by a slitting machine and a cutting machine to obtain the required composite coating electrode. After rolling, the active materials at the contact interface of the first coating and the second coating penetrate and cross-link each other.
[0067] In order to solve the above problems, an embodiment of the present invention provides a method for preparing a composite coating electrode, the preparation method comprising:
[0068] Step 1, preparing a slurry of a first coating layer and a slurry of a second coating layer;
[0069] The slurry of the first coating layer includes a first active material, a first conductive agent, and a first binder.
[0070] The first active material is a phosphorus-carbon composite material, and the mass percentage of the first active material is 70% to 95%, for example, 75%, 80%, 85%, 90%.
[0071] Phosphorus-carbon composite materials refer to phosphorus / carbon composite materials prepared by sublimation condensation method, high temperature adsorption method or high temperature ball milling method.
[0072] The first binder used in the first coating is one or a combination of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.
[0073] The first conductive agent includes at least one of conductive carbon black and carbon nanotubes.
[0074] The slurry of the second coating layer includes a second active material, a second conductive agent, and a second binder. The second active material is one or a combination of graphite, hard carbon, soft carbon, and lithium titanate, and the mass percentage of the second active material is 90% to 96%, for example, 91%, 92%, 93%, 94%, and 95%.
[0075] The second binder used in the second coating layer is at least one of CMC and SBR.
[0076] The second conductive agent includes at least one of conductive carbon black and carbon nanotubes.
[0077] Step 2, coating the dispersed slurry of the first coating layer on the negative electrode current collector and fully drying it;
[0078] The slurry of the first coating layer is coated on one surface of the negative electrode collector in a thickness direction of the negative electrode collector.
[0079] The first coating layer is coated by roller coating or spray coating.
[0080] The coating thickness of the first coating slurry is 15-45 μm.
[0081] Step 3, using the pole coil coated with the first coating as a substrate, coating the dispersed slurry of the second coating on the surface of the first coating, and fully drying;
[0082] The slurry of the second coating layer is coated on the outer surface of the first coating layer in the thickness direction of the negative electrode current collector.
[0083] The second coating layer may be coated by roller coating or spray coating.
[0084] The coating thickness of the second coating slurry is 20-60 μm.
[0085] Step 4, repeating steps 2 and 3 to complete double-sided coating of the negative electrode current collector, and obtaining the desired composite coating electrode after drying, rolling, slitting and cutting.
[0086] The dried pole coil is rolled using a roller press;
[0087] The electrode roll after rolling is cut and sliced by a slitting machine and a cutting machine to obtain the required composite coating electrode. After rolling, the active materials at the contact interface of the first coating and the second coating penetrate and cross-link each other.
[0088] In order to solve the above problems, an embodiment of the present invention further provides a battery, characterized in that it includes: a positive electrode, a separator, an electrolyte and the aforementioned composite coating electrode.
[0089] In an embodiment of the present invention, the active material in the positive electrode is at least one of nickel-cobalt-manganese or nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, and lithium iron oxide.
[0090] In an embodiment of the present invention, the diaphragm includes one of a polypropylene / polyethylene / polypropylene composite film (PP / PE / PP), a polyethylene film, a polypropylene film, a nylon cloth, a polyethylene film, a polyimide film, a polyethylene terephthalate, a cellulose film, a polyamide film, a poly(p-phenylene terephthalamide) film and a polyurethane fiber film.
[0091] In an embodiment of the present invention, the electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the solvent in the electrolyte is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; the additive in the electrolyte includes at least one of vinylene carbonate, propane sultone, carboxylates, succinonitrile and adiponitrile.
[0092] The battery includes an ion insertion / extraction battery, and specifically, the ions may be metal ions such as lithium ions, zinc ions, and magnesium ions.
[0093] The battery provided in the embodiment of the present invention adopts the aforementioned composite coating electrode as the negative electrode of the battery. During the operation of the battery, the second coating in the composite electrode coating can inhibit the expansion of the first coating (i.e., the phosphorus-carbon coating) to avoid the negative electrode active material (phosphorus-carbon composite material) from peeling off the current collector during a long cycle. Compared with a pure phosphorus-carbon electrode, the composite coating electrode provided in the embodiment of the present invention can improve the volume expansion problem of the phosphorus-carbon system battery and extend the battery cycle life.
[0094] The composite coating electrode of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.
[0095] Example 1
[0096] 1) A disperser is used to prepare the slurry for the first coating and the slurry for the second coating; the first active material raw material phosphorus carbon has a mass percentage of 90%, the binder raw material PAALi has a mass percentage of 5%, the total mass percentage of the conductive agent composed of conductive carbon black and carbon nanotubes is 5%, the second active material raw material graphite has a mass percentage of 93%, the binder raw material SBR+CMC has a mass percentage of 4%, and the total mass percentage of the conductive agent composed of conductive carbon black and carbon nanotubes is 3%).
[0097] 2) coating the dispersed first coating slurry on the current collector with a coating thickness of 15 μm (the current collector is copper foil), and fully drying (drying conditions: 90-110° C.);
[0098] 3) Using the pole coil coated with the first coating as the substrate, apply the dispersed second coating slurry on the surface of the first coating with a coating thickness of 45 μm, and fully dry (drying conditions: 90-110°C);
[0099] Repeat steps 2) and 3) to complete double-sided coating and drying of the current collector;
[0100] The dried pole coil is rolled using a roller press;
[0101] The electrode coil after rolling is cut and sliced by a slitting machine and a cutting machine to obtain the required composite coating electrode.
[0102] Battery assembly process
[0103] The positive electrode (active material (Li (Ni 0.6 Co 0.2 Mn 0.2 ) 2 )), a separator (PP / PE / PP) and the composite coating electrode of Example 1 were assembled as the negative electrode, encapsulated with an aluminum-plastic film, injected with an electrolyte (lithium hexafluorophosphate), prepared into a battery through chemical formation, and finally formed into a soft-pack battery, and the battery-related performance was tested.
[0104] Example 2
[0105] The difference between Example 2 and Example 1 is that the coating thickness of the first coating layer is 45 μm, the coating thickness of the second coating layer is 60 μm, and the rest is the same as Example 1.
[0106] Example 3
[0107] The difference between Example 3 and Example 1 is that the coating thickness of the first coating layer is 18 μm, the coating thickness of the second coating layer is 20 μm, and the rest is the same as Example 1.
[0108] Example 4
[0109] The difference between Example 4 and Example 1 is that the coating thickness of the first coating layer is 50 μm, the coating thickness of the second coating layer is 60 μm, and the rest is the same as Example 1.
[0110] Example 5
[0111] The difference between Example 5 and Example 1 is that the coating thickness of the first coating layer is 30 μm, the coating thickness of the second coating layer is 50 μm, and the rest is the same as Example 1.
[0112] Example 6
[0113] The difference between Example 6 and Example 5 is that the second active material raw material is hard carbon, the coating thickness of the second coating is 50 μm, and the rest is the same as Example 5.
[0114] Example 7
[0115] The difference between Example 7 and Example 6 is that the second active material raw material is soft carbon. The rest is the same as Example 6.
[0116] Comparative Example
[0117] 1) A disperser is used to prepare the slurry for the first coating; the first active material raw material phosphorus carbon has a mass percentage of 90%, the binder raw material PAALi has a mass percentage of 5%, and the total mass percentage of the conductive agent composed of conductive carbon black and carbon nanotubes is 5%.
[0118] 2) Coat the dispersed first coating slurry on the current collector with a coating thickness of 80 μm. The current collector is copper foil and is fully dried (drying conditions: 90-110° C.);
[0119] Repeat step 2) to complete double-sided coating and drying of the current collector;
[0120] The dried pole coil is rolled using a roller press;
[0121] The required negative electrode sheets are obtained by slitting and cutting the rolled electrode coils using a slitting machine and a cutting machine.
[0122] Battery assembly process
[0123] The positive electrode (active material (Li (Ni 0.6 Co 0.2 Mn 0.2 ) 2 )), the separator (PP / PE / PP) and the negative electrode sheet of the comparative example are assembled, packaged with an aluminum-plastic film, injected with an electrolyte (lithium hexafluorophosphate), and prepared into a battery through chemical formation, ultimately forming a soft-pack battery.
[0124] The relevant properties of the batteries prepared in Examples 1-7 and the comparative example were tested respectively, including the room temperature cycle performance and the full-charge thickness expansion. The specific test methods are as follows:
[0125] (1) Room temperature cycle performance test: At 25°C, the formed battery is charged to 4.3V with a constant current and constant voltage of 0.1C (cut-off current is 0.01C), and then discharged to 3.0V with a constant current of 0.1C. The capacity retention rate after 200 cycles of charge / discharge is calculated as follows:
[0126] Capacity retention rate after 200 cycles (%) = 200th cycle discharge capacity / 1st cycle discharge capacity × 100%.
[0127] The performance test results of the lithium ion batteries prepared in the above Examples 1-7 and Comparative Examples are shown in Table 1.
[0128] Table 1 Cycle performance of lithium ion batteries prepared in various embodiments and comparative examples
[0129] Battery cycle (200 times capacity retention) Example 1 95% Example 2 91% Example 3 95.5% Example 4 90% Example 5 91.5% Example 6 92% Example 7 92.5% Comparative Example 87%
[0130] It can be seen from Table 1 that, compared with the phosphorus-carbon single coating electrode as the negative electrode, the battery cycle performance is better when the composite coating electrode provided by the embodiment of the present invention is used as the negative electrode.
[0131] (2) Full-charge thickness expansion test: At 25°C, charge the formed battery to 4.3V using a 0.1C constant current and constant voltage test (cut-off current is 0.01C). Measure the thickness of the battery after charging. Then discharge the battery to 3.0V using a 0.1C constant current test. Measure the thickness of the battery after discharging.
[0132] Battery expansion rate (%) = (battery thickness at full charge - battery thickness before full charge) / battery thickness before full charge × 100%.
[0133] The expansion rates of the lithium ion batteries prepared in the above Examples 1-7 and Comparative Examples are shown in Table 2.
[0134] It can be seen from Table 2 that the composite coating electrode provided by the embodiment of the present invention, when used as a negative electrode, does have a good effect on improving the expansion of the battery.
[0135] Table 2 Expansion rate of lithium ion batteries prepared in various embodiments and comparative examples
[0136] Battery expansion rate Example 1 19% Example 2 29% Example 3 22% Example 4 33% Example 5 27% Example 6 22% Example 7 25% Comparative Example 36%
[0137] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0138] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A composite coating electrode, characterized in that: include: Anode current collector; A first coating layer attached to the surface of the negative electrode current collector, wherein the first coating layer comprises a first active material, and the first active material is a phosphorus-carbon composite material; The second coating layer is attached to the surface of the first coating layer, and the second coating layer includes a second active material, and the thermal expansion coefficient of the second active material is smaller than the thermal expansion coefficient of the first active material.
2. The composite coating electrode according to claim 1, characterized in that: The second active material is at least one of graphite, hard carbon, soft carbon, and lithium titanate.
3. The composite coating electrode according to claim 1, characterized in that: The mass percentage of the first active substance is 70% to 95%.
4. The composite coating electrode according to claim 2, characterized in that: The mass percentage of the second active substance is 90% to 96%.
5. The composite coating electrode according to any one of claims 1 to 4, characterized in that: The first coating has a thickness of 15 to 45 μm.
6. The composite coating electrode according to any one of claims 1 to 4, characterized in that: The second coating has a thickness of 20 to 60 μm.
7. The composite coating electrode according to any one of claims 1 to 4, characterized in that: The first coating layer includes a first binder, and the first binder is at least one of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.
8. The composite coating electrode according to any one of claims 1 to 4, characterized in that: The second coating layer includes a second binder, and the second binder is at least one of CMC and SBR.
9. The composite coating electrode according to any one of claims 1 to 4, characterized in that: The negative electrode current collector is at least one of copper foil, aluminum foil or carbon-coated aluminum foil.
10. A method for preparing a composite coating electrode according to any one of claims 1 to 9, characterized in that: The preparation method comprises: 1) preparing a slurry for the first coating layer and a slurry for the second coating layer; 2) coating the dispersed slurry of the first coating layer on the negative electrode current collector and fully drying it; 3) Using the pole coil coated with the first coating as the substrate, coating the dispersed slurry of the second coating on the surface of the first coating, and fully drying; Repeat steps 2) and 3) to complete double-sided coating of the negative electrode current collector, and obtain the desired composite coating electrode after drying, rolling, slitting and cutting.
11. The method for preparing a composite coating electrode according to claim 10, characterized in that: The first coating layer and / or the second coating layer may be coated by roller coating or spray coating.
12. The method for preparing a composite coating electrode according to claim 10, characterized in that: The coating thickness of the first coating slurry is 15-45 μm; the coating thickness of the second coating slurry is 20-60 μm.
13. A battery, characterized in that: include: A positive electrode, a separator, an electrolyte, and a composite coating electrode as described in any one of claims 1 to 9.
